2010
DOI: 10.1186/1471-2474-11-279
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of carbonic anhydrase I in the synovium of patients with ankylosing spondylitis

Abstract: BackgroundOne of the most distinctive features of ankylosing spondylitis (AS) is new bone formation and bone resorption at sites of chronic inflammation. Previous studies have indicated that the hyperplasia and inflammation of synovial tissues are significantly related to the pathogenic process of AS. The present study used a proteomic approach to identify novel AS-specific proteins by simultaneously comparing the expression profiles of synovial membranes from patients with AS, rheumatoid arthritis (RA) and os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 25 publications
2
47
0
1
Order By: Relevance
“…Data also indirectly point to low-pH-dependent reduction in the proliferation of lymphocytes and polymorphs, impaired chemotaxis and inhibition of antibody production 3 . Several forms of carbonic anhydrases (CAs, EC 4.2.1.1), metalloenzymes that reversibly catalyze the conversion of CO 2 to the bicarbonate ions and protons 4 , have been recognized in articular diseases, including CA I which is over-expressed in the synovium of the patients with ankylosing spondylitis 5 . Transgenic mice over-expressing CA I showed aggravated joint inflammation and destruction 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Data also indirectly point to low-pH-dependent reduction in the proliferation of lymphocytes and polymorphs, impaired chemotaxis and inhibition of antibody production 3 . Several forms of carbonic anhydrases (CAs, EC 4.2.1.1), metalloenzymes that reversibly catalyze the conversion of CO 2 to the bicarbonate ions and protons 4 , have been recognized in articular diseases, including CA I which is over-expressed in the synovium of the patients with ankylosing spondylitis 5 . Transgenic mice over-expressing CA I showed aggravated joint inflammation and destruction 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al 23 investigated the levels of expression of CA1 by proteomic approach and suggested that CA1 may promote improper calcification and bone resorption in the synovium of patients with ankylosing spondylitis. In addition, the concentrations of CA1 and Zn in the red blood cell can be useful in estimating the extent of increased levels of thyroid hormone in patients with hyperthyroidism, and further distinguish patients with hyperthyroid GD from those with transient thyrotoxicosis 24…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concentration of CA I in synovial fluids is higher in patients with ankylosing spondylitis than in patients with osteoarthritis and rheumatoid arthritis. These findings suggest that overexpression of CA I in the synovial tissues of ankylosing spondylitis patients may promote ectopic calcification [59]. In addition, the carbonic anhydrase inhibitor methazolamide has been used to treat active ankylosing spondylitis and it has been suggested that it may improve clinical symptoms by inhibiting carbonic anhydrase activity during the processes of bone resorption and new bone formation [60].…”
Section: Carbonic Anhydrase and Soft-tissue Calcificationmentioning
confidence: 97%